Staging for vaginal cancer. Issue 6 (August 2015) - Rajaram, Shalini; Maheshwari, Amita; Srivastava, Astha
<x xml:space="preserve">Abstract</x> Vaginal cancer is a rare cancer comprising about 3% of all gynecologic cancers. Primary vaginal cancer should be carefully assigned as spread from cervix, vulva, and other metastatic tumors to vagina can occur. Although vaginal cancer traditionally occurs in older postmenopausal women, the incidence of high-risk human papillomavirus (HPV)-induced cancers is increasing in younger women. Squamous cell carcinoma is still the most common histopathologic type followed by adenocarcinoma. With decreasing use of diethylstilbestrol in pregnancy, non-diethylstilbestrol-associated cancers are described. The Federation Internationale de Gynecologie et d'Obstetrique (FIGO) staging of vaginal cancer (2009) follows the same rules as cervical cancer; it is clinically staged and allows the use of routine investigative modalities for staging. Although FIGO encourages the use of advanced imaging modalities, such as computed tomography, magnetic resonance imaging (MRI), and positron emission tomography (PET), to guide therapy, the imaging findings may not be used to change or reassign the stage. TNM staging is the pathologic staging system proposed by the American Joint Committee on Cancer, and information available from examination of the resected specimen, including pelvic and inguinal lymph nodes, may be used for staging.